2007
DOI: 10.1044/0161-1461(2007/024)
|View full text |Cite
|
Sign up to set email alerts
|

Narrative and Vocabulary Development of Bilingual Children From Kindergarten to First Grade: Developmental Changes and Associations Among English and Spanish Skills

Abstract: Purpose-Research has identified English oral language proficiency as being critical for bilingual students' literacy development. This study examines developmental patterns and associations among oral vocabulary and narrative skills in a longitudinal sample of 24 Spanish/English bilingual children from low socioeconomic backgrounds so as to further our understanding of the development of oral proficiency.Method-English and Spanish data were gathered using standardized vocabulary tests and narrative elicitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
257
2
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(294 citation statements)
references
References 20 publications
21
257
2
14
Order By: Relevance
“…Previous cross-sectional and longitudinal studies on the English narratives of Spanish-English bilingual children have demonstrated that both microstructure and macrostructure improve as children progress from preschool to the early school-age years (e.g., Muñoz, Gillam, Peña, & Gulley-Faehnle, 2003;Rojas & Iglesias, 2013;Squires et al, 2014;Uccelli & Páez, 2007). However, the factors that may support narrative development have not been widely investigated.…”
Section: Narrative Assessment In Young Children: Microstructure and Mmentioning
confidence: 95%
“…Previous cross-sectional and longitudinal studies on the English narratives of Spanish-English bilingual children have demonstrated that both microstructure and macrostructure improve as children progress from preschool to the early school-age years (e.g., Muñoz, Gillam, Peña, & Gulley-Faehnle, 2003;Rojas & Iglesias, 2013;Squires et al, 2014;Uccelli & Páez, 2007). However, the factors that may support narrative development have not been widely investigated.…”
Section: Narrative Assessment In Young Children: Microstructure and Mmentioning
confidence: 95%
“…136-137). This process of language loss and shift occurs rapidly once these children have experienced their first exposure to the broader English-speaking community and begin to attend school (deVries, 1999;Uccelli & Paez, 2007). In this window of time young ELL may find themselves in linguistic limbo (Glennen, 2002) just as they are about to make their initial steps into emergent and early literacy development in K-grade 2 and beyond.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One promising approach is to elicit spontaneous narrative from a prompt such as a wordless picture storybook. Profiling narrative output along such measures as total number of words (T), number of words (NDW), and type-token ratio (T divided by NDW) has been the most common approach (Reich & Reich, 1977;Watkins & Kelly, 1995;Uccelli & Paez, 2007). However, these measures have generally not been found sensitive indicators of English narrative productivity.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This claim also applies to Latino bilingual children from the United States. Findings on monolingual Spanish speakers' narratives might prove relevant for bilingual children, particularly given research that P1: jsy Top Margin: 0.3764in Gutter Margin: 0.87828in CUUS321-08 cuus321/mccabe ISBN: 978 0 521 88375 7 May 21, 2008 21:26 Beyond Chronicity 203 suggests transfer of narrative structure skills across languages (Pearson, 2002;Uccelli & Páez, 2007). However, Latino children in the United States come from different countries, from families with various characteristics, and from different language-socialization patterns.…”
Section: %)mentioning
confidence: 99%